2021
DOI: 10.3748/wjg.v27.i21.2910
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of hepatic inflammation in chronic hepatitis B patients with a random forest-backward feature elimination algorithm

Abstract: BACKGROUND Persistent liver inflammatory damage is the main risk factor for developing liver fibrosis, cirrhosis, and even hepatocellular carcinoma in chronic hepatitis B (CHB) patients. Thus, accurate prediction of the degree of liver inflammation is a high priority and a growing medical need. AIM To build an effective and robust non-invasive model for predicting hepatitis B-related hepatic inflammation. METHODS A total of 650 treatment-naïv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…The exploration of subgroups/interactions analyses and control for confounding were extremely important for a scientific study, according to STROBE statement 22 . Unfortunately, besides the above two studies, the other three studies were also not involved 15,25,26 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The exploration of subgroups/interactions analyses and control for confounding were extremely important for a scientific study, according to STROBE statement 22 . Unfortunately, besides the above two studies, the other three studies were also not involved 15,25,26 …”
Section: Discussionmentioning
confidence: 99%
“…22 Unfortunately, besides the above two studies, the other three studies were also not involved. 15,25,26 Besides the role mentioned above, there were numerous values of qAnti-HBc in the diagnosis and treatment monitoring of hepatitis B. These include the following values: identification of the natural history of hepatitis B (immune-tolerant phase was lower compared to immune-clearance phase) 12,27 ; positive correlation with liver fibrosis stage (used to help diagnose significant fibrosis) 28,29 ; positive correlation with HBeAg seroconversion after interferon 13,30 or T A B L E 4 Relationship between qAnti-HBc and Ishak score of HAI in patients receiving entecavir-based therapy followed to 78 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is mounting evidence that qAnti-HBc level not only correlates positively with the severity of liver inflammation but also decreases with the improvement of inflammation severity in patients receiving therapy [ 19 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. It was shown that serum qAnti-HBc level, ALT and liver inflammation activity were closely related [ 44 , 47 ]. The background of this association is the interplay between the virus and the host’s immune system.…”
Section: Clinical Utility Of Qanti-hbcmentioning
confidence: 99%